Polymyxin b therapy for multidrug resistant gram negative infections : outcome and risk factors for treatment failure in critical care - Ismail, Bahiah (2015)

(untitled)
Objective: Polymyxins have re-administered in clinical practice due to the dry antibiotic development pipeline and worldwide increasing infections caused by multi-drug resistant (MDR) gram negative bacteria. The aim of this study is to investigate the use of polymyxin B antibiotic therapy in Intensive Care Unit, Hospital Universiti Sains Malaysia (HUSM) and to identify the risk factors for polymyxin B treatment failure. Outcomes will be classified into clinical cure and clinical failure. Methodology: This was a crossectional study using secondary data done in Intensive Care Unit (ICU) Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan. This study involved 96 cases of gram negative infections (blood-stream infection and pneumonia), particularly Acinetobacter spp, Acinetobacter baumanii, Klebsiella pneumonia and Pseudomonas aeruginosa, isolated from blood, endotracheal aspirate (ETA) as well asbronchoalveolar lavage (BAL) sample, all were treated with iv polymyxin B. The patient selections were from pharmacy databank on polymyxin B usage from 1 January 2010- 31 December 2014. Ninety-six cases treated with polymyxin B from ICU were randomly selected and their medical record were traced from Record Office and reviewed. Their demographic profiles, underlying diseases, potential risk factors, antibiotic usage, possible adverse effects, microbiology results and outcome were reviewed. Results: Clinical outcome was evaluated for the 96 samples. Clinical cure contributed to 51% of the cases (49 cases) meanwhile another 47 cases (49%) contributed to clinical failure. Percentage of clinical cure was slightly higher compared to clinical failure for this study. 47 clinical failure subject (49.0%) reported death and all were referred to attributable mortality. Associated risk factors for polymyxin B treatment failure by Multiple Logistic Regression model were primary bacteremia (p=0.005) and inappropriate dose of polymyxin B (p=0.005). Polymyxin B was well tolerated by almost all of our sample, whereby only 7 out of 96 cases experienced deteriorating renal function, and it was not lead to discontinuation of the treatment.. Conclusions: In conclusion, mortality associated with multidrug resistant gram negative pathogens continues to be high. The early susceptibility, prompt and optimal antibiotic such as polymyxin B and also combination of antibiotic in particular with sulperazaone seems to have a survival benefit in this critically ill population.